Motivasi Belajar Siswa Kelas V di SD Negeri 13 Tanjung Batu - Mutiah, Cici Sanita; Hatim, Magdad; Suryani, Ida (Jurnal Ilmiah Dikdaya, 2024)
This research was motivated by a lack of learning motivation given by teachers to fifth grade students which was carried out at SD 13 Tanjung Batu. This research aims to determine the motivation of fifth grade students at SD 13 Tanjung Batu in participating in Mathematics learning. This research is a qualitative descriptive study. The method used is qualitative with data collection techniques using triangulation. The subjects of this research were all class V students at SD 13 Tanjung Batu, totaling 30 students. The data analysis technique uses qualitative descriptive analysis using the Miles and Huberman model. The results of the research show that the motivation of class V students in participating in Mathematics learning at SD Negeri 13 Tanjung Batu in learning Mathematics, there are 77.5% of students who are happy. The majority of students agree and strongly agree to doing questions (78%) and doing homework (73%). Apart from that, the majority of students also agreed and strongly agreed that they could get good grades (77.5%). Students' awareness of learning was 74.6%. As many as 70% of students (13 students) strongly disagree with cheating.